Perencanaan Perhitungan AKNOP pada Daerah Irigasi Mrican Sebagai Upaya Peningkatan Kinerja Irigasi - Erna Tri Asmorowati; Diah Sarasanty (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
Food security is one of the targets of the Sustainable Development Goals that must be achieved by 2030. One of the problems faced in achieving this target is the decrease in the function of irrigation infrastructure by ± 70%, resulting in the reduced water supply to agricultural land. The purpose of this research is to recalculate the operational and maintenance needs of the Mrican Irrigation Area by the applicable regulations and the current conditions of the study area for the needs of the 2021 budget year. The research was conducted in the Mrican Irrigation Area with an area of ​​30,341 ha located in 3 districts, namely Kediri, Nganjuk and, Jombang. The result of optimization calculation of personnel for operational activities and maintenance of irrigation networks in the Mrican Irrigation Area is 577 people. The length of the carrier line is 366 km and the drainage is 248 km long. The number of waterworks is as many as 966 units. The results of calculations and analyzes that have been carried out, it is found that the amount of the Operational and Maintenance Real Needs of Mrican Irrigation Area for the irrigation operational management component is Rp. 6,329,767,232, the component of surface irrigation operation costs Rp. 31,490,208,724, and the maintenance component of the surface irrigation network is Rp. 22,685,844,371. The total cost of the Operational and Maintenance Real Needs of Mrican Irrigation Area is Rp. 60,505,820,327.